Diagnostic Value of Direct Antibiotic Susceptibility Test for Faster BacterialSusceptibility Reporting in Bacteremia - Rebriarina Hapsari; Vincentia Rizke Ciptaningtyas; Masfiyah Masfiyah (Sains Medika, 2012)
Background: Rapid and accurate information on susceptibility of bacteria causing bacteraemia is very helpful in sepsis management. Blood culture is the gold standard for bacteraemia diagnosis. Standard antibiotic susceptibility testing needs at least three days for completion while direct method can give the result a day earlier. The aim of this study was to investigate the diagnostic value of direct antibiotic susceptibility testing in blood culture. Methods: Bloods from positive BACTEC bottles which met inclusion and exclusion criteria were put into sterile tubes and centrifuged. The pellets were then used to make 0.5 McFarland bacterial suspensions and directly used for antibiotic susceptibility testing. Interpretations of direct method were compared to standard method to count sensitivity, specificity, sensitive predictive value, resistant predictive value, accuracy, and kappa value.